Examining Undergraduate Students' Attitudes toward Business Statistics in the United States and China. (19th July 2018) - Wang, Ping; Palocsay, Susan W.; Shi, Jinyan; White, Marion M.
ABSTRACT: The rapid growth of analytics is bringing more attention to quantitative core curriculum requirements in undergraduate business programs. Statistical knowledge and skills are unequivocally recognized as essential cornerstone of business analytics. Furthermore, educational research has shown that academic performance in statistics classes is related to the attitudes that students bring to the course. This article assesses the reliability and validity of the Survey of Attitudes toward Statistics (SATS) in measuring noncognitive dimensions of attitudes among undergraduate business students. Sample data from U.S. and Chinese introductory business statistics classes were collected and analyzed to learn more about this aspect of student engagement across business schools located in countries with substantially different levels of success in international mathematics achievement testing, as well as differing cultural and educational practices. Results show that the six‐factor model structure of the SATS provides a good fit in both populations, with students entering business statistics holding only slightly positive attitudes toward the subject. Significant distinctions between four of the six attitude components were identified. Implications of measuring and improving these attitudes are discussed. Business statistics instructors are encouraged to use the survey as a standardized instrument to measure effects of interventions and make evidence‐based pedagogical decisions.